Smokeless Tobacco and Its Ill-Effects: Recent Literature Update - Singhavi, Hitesh R.; Singh, Arjun; Chaturvedi, Pankaj (Indian Journal of Medical and Paediatric Oncology, 2021)
According to the Global Adult Tobacco Survey part 2 (GATS-2), approximately 200 million adult Indians consume smokeless tobacco (SLT). Circumvention of SLT product ban has been observed. We conducted a review of the literature to summarize the ill effects of tobacco for the articles published from 2019 to 2020. A systematic search of the databases PubMed (2019 onward) and Web of Science (2019 onward), through February 2021 was done. Search yielded 1,061 articles and after excluding articles based on the inclusion criteria, 37 articles were taken in to consideration. The review shows that differential SLT product has specific odds of oral carcinogenesis. Review also indicates the emerging data of cardiovascular risk due to higher use of SLT products along with its known cause of oral cancer. It also cautions about the adverse consequences of pregnancy associated with SLT use.
Keywords: smokeless tobacco; gutkha; oral cancer; cancer